2020
DOI: 10.3390/molecules25225425
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Beta-Blocker Drug–Drug Interactions with Fibrinogen Blood Plasma Protein: A Computational and Experimental Study

Abstract: In this work, one of the most prevalent polypharmacology drug–drug interaction events that occurs between two widely used beta-blocker drugs—i.e., acebutolol and propranolol—with the most abundant blood plasma fibrinogen protein was evaluated. Towards that end, molecular docking and Density Functional Theory (DFT) calculations were used as complementary tools. A fibrinogen crystallographic validation for the three best ranked binding-sites shows 100% of conformationally favored residues with total absence of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
(228 reference statements)
0
4
0
Order By: Relevance
“…Thus, polypharmacological therapies are arguably more efficient by targeting multiple disease-associated viral genes ( Paolini et al, 2006 ; Apsel et al, 2008 ; Hopkins, 2008 ; Hopkins, 2009 ). Identifying proper target combinations and designing effective multi-targeting agents require approaches such as in silico drug design, which provides a powerful tool to speed up chemical compound screening ( Chaudhari et al, 2017 ; Peng et al, 2018 ; Balasubramaniam and Reis, 2020 ; González-Durruthy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, polypharmacological therapies are arguably more efficient by targeting multiple disease-associated viral genes ( Paolini et al, 2006 ; Apsel et al, 2008 ; Hopkins, 2008 ; Hopkins, 2009 ). Identifying proper target combinations and designing effective multi-targeting agents require approaches such as in silico drug design, which provides a powerful tool to speed up chemical compound screening ( Chaudhari et al, 2017 ; Peng et al, 2018 ; Balasubramaniam and Reis, 2020 ; González-Durruthy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the structural point of view, the entire length of the FIB molecule can be divided into three major portions (Figure S1), of which the N-terminal central region is called the E-region, which is found to be the most favorable pocket for ligand binding. The main funnel hydrophobic cavity (called pocket 1) is the main binding site of the E-region, corresponding to the thrombin-binding domain. , All the drugs bind within the multiple cavities densely located in the N-terminal central nodule E-region. In general, this suggests that the interactions (Table S1) fit with a spontaneous thermodynamic process, as indeed manifested in the negative Δ G values.…”
Section: Discussionmentioning
confidence: 99%
“…FIB is a soluble glycoprotein composed by disulfidelinked dimer of three nonidentical polypeptide chains, Aα, Bβ, and γ [52]. Previous results showed that multiple cavities more densely located in the N-terminal central nodule E-region of FIB corresponded to the thrombin binding-domain, which have critical importance for the blood coagulation process [53]. Therefore, the molecular docking simulations focused on the potential docking interaction between L-GSH and L-Cys with E-region of FIB.…”
Section: Molecular Docking Analysis Of L-gsh and L-cys With Proteinsmentioning
confidence: 99%